2014
DOI: 10.11120/ened.2014.00020
|View full text |Cite
|
Sign up to set email alerts
|

Outcome-based Education – The Assessment of Programme Educational Objectives for an Engineering Undergraduate Degree

Abstract: Outcome-based Education (OBE) emphasises on two main components in terms of student achievement in an academic programme. One is the Programme Outcomes (POs) which is measured at the point of graduation, and the other, the Programme Educational Objectives (PEOs) is assessed over a longer period of time (around 4-5 years) after graduation. This study focuses on the establishment of a systematic procedure adopted by the Department of Mechanical, Materials and Manufacturing Engineering at the University of Nottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 6 publications
(6 reference statements)
0
27
0
5
Order By: Relevance
“…The effect of learning refers to whether students have the ability to discover and solve problems or not [21,22], whether they have the ability of comprehensive analysis, and the ability of innovative research and development is particularly important in the context of emerging engineering education.…”
Section: Experimental Inspection Phasementioning
confidence: 99%
“…The effect of learning refers to whether students have the ability to discover and solve problems or not [21,22], whether they have the ability of comprehensive analysis, and the ability of innovative research and development is particularly important in the context of emerging engineering education.…”
Section: Experimental Inspection Phasementioning
confidence: 99%
“…K.Y. Tshai, et al, 2014 concluded that determining students' satisfaction level in their attainment of PEO is an essential part in closing the loop (CDL) of the continual quality improvement (CQI) process within the context of OBE.…”
Section: Introductionmentioning
confidence: 99%
“…Wong et al [10] implemented OBE from the program design perspective and discusses importance of OBE in teaching. Tshai et al [11] formulated the OBE process in integration with stakeholders and identified set of strategies for continuous quality improvement (CQI). The authors discussed an OBE framework and implemented it in Object-Oriented Software Development course [12].…”
Section: Introductionmentioning
confidence: 99%